Da’i Peduli Institution: Historical Trajectory and Its Role in Humanitarian Social Movement Dynamics, 2014–2025 - Mhd. Salim Mahallin; Nabila Yasmin (Mahesa Research Center (PT. Mahesa Global Publishing), 2026)
This study examines the history, development, and humanitarian social movement model of Lembaga Dai Peduli from 2014 to 2025. Founded by alumni from the Middle East, the institution integrates da’wah and social action through the principles of dakwah bil hal (action-based preaching) and idkhalus surur (bringing happiness to others). The movement focuses on two main areas: international humanitarian assistance for Palestine and domestic programs, including disaster response and the empowerment of dai in Indonesia. The distinctive feature of this movement lies in its positioning of dai not merely as religious messengers, but as multidimensional humanitarian actors operating at the grassroots level. Employing a qualitative approach through in-depth interviews, observation, and document analysis, this research reconstructs the historical trajectory of the institution, analyzes its strategies for integrating da’wah and humanitarian work, and examines its contributions to religious social movements in Indonesia. The findings indicate that Lembaga Dai Peduli has developed a hybrid model of faith-based humanitarian activism by institutionalizing grassroots-oriented dai empowerment and fostering transnational solidarity for Palestine. This model strengthens the role of religious actors within contemporary humanitarian social movements in Indonesia. These results contribute to broadening the analytical framework of religion-based social movements while also offering practical insights for the development of similar grassroots initiatives.